2007
DOI: 10.1111/j.1539-6975.2007.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Eclectic Paradigm: Evidence From the U.S. Reinsurance Market

Abstract: This study provides a test of the eclectic paradigm with data from U.S. reinsurers. The U.S. reinsurance industry provides a unique setting to test the eclectic paradigm due to the extensive data available on U.S. reinsurers and the well-developed literature related to reinsurance. The ability to test the hypotheses related to the eclectic paradigm in a service industry and incorporate industry-specific factors adds to the eclectic paradigm literature which has traditionally focused primarily on manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 40 publications
1
42
0
2
Order By: Relevance
“…Beyond the simple decision of whether foreign entry is allowed or not, foreign banks are more likely to establish subsidiaries or affiliates in locations with fewer restrictions on their activities. Government effectiveness is included in the study by Cole, Lee, and McCullough (2005) to determine the potential relation to the regulatory environment.…”
Section: Determinants Of International Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the simple decision of whether foreign entry is allowed or not, foreign banks are more likely to establish subsidiaries or affiliates in locations with fewer restrictions on their activities. Government effectiveness is included in the study by Cole, Lee, and McCullough (2005) to determine the potential relation to the regulatory environment.…”
Section: Determinants Of International Presencementioning
confidence: 99%
“…Ma and Pope found that countries with higher GDP tend to attract more international insurers participation 20 . A more recent article by Cole, Lee, and McCullough (2005) provides a comprehensive approach to the decision process of U.S. reinsurers to assume from foreign insurers based on the OLI paradigm. The results of the study provide support to firm‐specific factors and location‐specific advantages.…”
Section: Determinants Of International Presencementioning
confidence: 99%
“…The model has also been evaluated for service industries, such as the reinsurance industry (Cole et al, 2007). Even for service industry firms, a complete picture of the decision to internationalise could be obtained by integrating firm-, country-and industry-specific factors (Cole et al, 2007). Thus, conceptually and empirically, the eclectic model has remained a good framework for evaluating internationalisation.…”
Section: Dunning's Eclectic Modelmentioning
confidence: 98%
“…In terms of industrial applicability, a significant number of studies using the eclectic model have focused on goods manufacturing firms. The model has also been evaluated for service industries, such as the reinsurance industry (Cole et al, 2007). Even for service industry firms, a complete picture of the decision to internationalise could be obtained by integrating firm-, country-and industry-specific factors (Cole et al, 2007).…”
Section: Dunning's Eclectic Modelmentioning
confidence: 99%
“…30 . 31 Ward and Zurbruegg (2002), Beck and Webb (2003), Li et al (2006), Cole et al (2007) and . 32 Thanks to two anonymous referees for pointing out these factors.…”
Section: Review Of the Existing Literaturementioning
confidence: 99%